Southern marsh deer (Blastocerus dichotomus) populations assessed using Amplicon Sequencing on fecal samples - Wolfenson, Laura Irene (2024)
Populations in isolated and small fragments lose genetic variability very fast and are usually of conservation concern because they are at greater risk of local extinction. The largest native deer in South America, Blastocerus dichotomus (Illiger, 1815), is a Vulnerable species according to the IUCN categorization, which inhabits tropical and subtropical swampy areas. In Argentina, its presence has been restricted to four isolated fragments. Here we examine the genetic diversity and differentiation among three of them, including the three different patches that form the southernmost population, using 18 microsatellite markers genotyped by Amplicon Sequencing of DNA extracted from fecal samples. Genetic diversity was low (HE < 0.45) in all three populations studied. We found three genetic clusters compatible with the geographic location of the samples. We also found a metapopulation dynamics that involves the patches that make up the southernmost population, with evidence of a barrier to gene flow between two of them. Our results point to the creation of a corridor as a necessary and urgent management action. This is the first study, at the population level, employing microsatellite genotyping by Amplicon Sequencing with non-invasive samples in an endangered species.